The Communication Rings: A Tool for Exploring the Social Networks of Individuals with Hearing Loss - Montano, Joseph J.; AlMakadma, Hamamm (Seminars in Hearing, 2012)
Social networks have a positive effect on the self-management of chronic health conditions. The Communication Rings, developed by faculty, staff, and participants at the Ida Institute, is a tool developed to help the audiologist identify the communication networks of their patients with hearing loss. It encourages individuals to consider the people who are important parts of their lives and the impact hearing loss may have on those relationships. This article discusses the development of the tool, instructions for use, and its application for clinical and academic purposes.
Keywords: Aural rehabilitation; social networks; significant other; counseling; hearing loss